Time-Invariant Fuzzy Max-Plus Linear Systems - Marcellinus Andy Rudhito (Jurnal Matematika & Sains, 2012)
In time-invariant max-plus linear systems (IMLS), the activity times are real numbers. In time-invariant fuzzy max-plus linear systems (IFMLSI), as there is uncertainty in the activity times, the activity times are modeled as fuzzy numbers. This article discusses a generalization of IMLSI to IFMLS, especially IFMLS with single input single output (SISO), and input-output analysis of IFMLS-SISO. We show that input-output analysis IFMLS-SISO associated with the latest times input problem can be solved by using a solution of a system of fuzzy number max-plus linear equations. Keywords: Linear Systems, Max-Plus, Fuzzy Number, Time-Invariant, Input-Output. Â  Sistem Linier Max-Plus Samar yang Invarian terhadap Waktu Abstrak Dalam sistem linear max-plus waktu invarian (SLMI), waktu aktifitas berupa bilangan real. Dalam sistem linear max-plus kabur waktu invarian (SLMKI), ada ketidakpastian dalam waktu aktifitas, sehingga waktu aktifitas dimodelkan sebagai bilangan kabur. Artikel ini membahas suatu generalisasi SLMI menjadi SLMKI, khususnya SLMKI dengan satu input dan satu output (SISO), dan analisis input-output SLMKI-SISO. Dapat ditunjukkan bahwa analisis input-output SLMKI-SISO yang berkaitan dengan masalah waktu input paling lambat, dapat diselesaikan dengan menggunakan suatu penyelesaian sistem persamaan linear max-plus kabur. Kata kunci: Sistem Linear, Max-Plus, Bilangan Kabur, Waktu-Invariant, Input-Output.